2014
DOI: 10.1103/physreva.90.043415
|View full text |Cite
|
Sign up to set email alerts
|

Ejection of innershell electrons induced by recollision in a laser-driven carbon atom

Abstract: Ejection of core electrons as a result of recollision in a laser-driven carbon atom is theoretically investigated with a quasiclassical model. The model, called "fermionic molecular dynamics," gives rise to a ground-state carbon atom where the six electrons are paired in shells, with different binding energies. This feature renders possible, on a classical level, the discussion of the ejection of electrons from different shells. By analyzing a large number of trajectories of a carbon atom exposed to an intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 104 publications
(180 reference statements)
1
8
0
Order By: Relevance
“…Time evolution of the system is governed by Hamilton’s equations of motion where c is the speed of light, and the laser electric field, E ( t , r ), and magnetic field, B ( t , r ), are given by where with the laser field strength E 0 , angular frequency ω 0 corresponding to a wavelength of 800 nm, CEP φ, and pulse length T 0 = 2π n c /ω 0 ; n c being the number of optical cycles chosen to be 3 for 7.9 fs pulse width similar to ref .…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Time evolution of the system is governed by Hamilton’s equations of motion where c is the speed of light, and the laser electric field, E ( t , r ), and magnetic field, B ( t , r ), are given by where with the laser field strength E 0 , angular frequency ω 0 corresponding to a wavelength of 800 nm, CEP φ, and pulse length T 0 = 2π n c /ω 0 ; n c being the number of optical cycles chosen to be 3 for 7.9 fs pulse width similar to ref .…”
Section: Theoretical Modelmentioning
confidence: 99%
“…A stable quasiclassical ground-state configuration of atoms has been obtained using this FMD model and this method has already been extensively applied in studying various atomic and molecular processes including description of atoms , and molecules in intense laser fields. Moreover, it was successful in achieving reasonable qualitative agreement with experimental results. , Recently, this FMD model was employed to understand the many-electron response of the carbon atom to intense laser fields …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…V H mimics the effect of the Heisenberg uncertainty principle that demands that a particle cannot be localized in position and momentum simultaneously. The FMD model has already been extensively applied to study the laser-induced dynamics of atoms, , molecules, clusters, and atom–ion collision processes. Within this quasi-classical method, Huang et al have investigated the electron momentum distribution from H 2 + by a circularly polarized laser pulse . By back analysis of the trajectories, they showed that most of the electrons are emitted with a time lag of hundreds of attoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…25 V H mimics the effect of the Heisenberg uncertainty principle that demands that a particle cannot be localized in position and momentum simultaneously. The FMD model has already been extensively applied to study the laser-induced dynamics of atoms, 22,26 + by a circularly polarized laser pulse. 32 By back analysis of the trajectories, they showed that most of the electrons are emitted with a time lag of hundreds of attoseconds.…”
Section: Introductionmentioning
confidence: 99%